DARI ISLAM RADIKAL KE ISLAM PLURALIS GENEALOGI GERAKAN PADERI DAN PENGARUHNYA TERHADAP ISLAM PLURALIS DI PERBATASAN MINANGKABAU - Syafwan Razi (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2015)
Dialectics of religion and social reality can be seen as one of the factors driving the emergence of religious movements. Social reality in the community can lead to the interpretation of typical social movements with basicly social implication. Thus, the radical religious movement grows as a backlash against perceived unjust structures and threatens its existence. Polemics about Padri movement in the Minangkabau as a radical movement must be thoroughly understood and not partially, through the study of history with genealogical approach, interpreting the history of this war will not merely in the sense of time, space, and actor. By tracing genealogy of this religious movement lead us to understand change of identity and historical facts that speak another. Allegations that the Padri movement is extreme and radical to be deeply reconsidered. In fact, the Padri movement has been instrumental in creating a religious understanding of Islamic societies tend Minangkabau northern frontier in the puritanical religious understanding, more pluralist because it is inhabited by several ethnic and even religious, and most importantly between customary and religious accommodation. Under this approach, especially genealogy postmodernism and identity, this paper will examine the history and influence of the Padri movement toward religious understanding Minangkabau societys northern frontier.Keyword: Radical Islam, Pluralist Islam, Genealogy of Paderi Movement